Analysis of Delay Due to Railway Level Crossings - Aliansyah, Aldi; Rulhendri, Rulhendri; Alimuddin, Alimuddin (ASTONJADRO, 2026)
Depok City is one of the buffer cities of the nation's capital, because the distance is only about 29 km from DKI Jakarta. With the many vehicles, Depok City has become one of the cities with moderate to high levels of congestion. The congestion is also supported by other highway network system problems, namely delays caused by railroad crossings. The aim is to investigate the delays that arise due to the intersection between the road and the railroad on Jl. Raya Citayam, Depok City using the shock wave method and looking for a comparison of traffic volume between weekdays and holidays. The method for being able to perform data analysis, then all the data needed must have been obtained. Data collection of flow/volume and travel time is carried out when the crossing gate is open and no trains are crossing. Then the flow/volume data is processed using the Microsoft Excel program. The EKR value is used to convert the vehicle traffic flow unit into Light Vehicle Units (SKR). The next step is to calculate the speed based on the travel time that has been obtained. Next, look for the mathematical relationship between flow, speed, and density in order to obtain the speed when the flow is free (Sff) and density (Dj). The Sff and Dj values ​​are then used to find the VM and DM values. The VM and DM values ​​are then used to calculate the shock wave value. The shock wave value obtained can be used to obtain the delay that occurs. From the results of the analysis and calculation of traffic flow volume, the minimum result is obtained on Monday at 14 pcu/hour and the maximum occurs on Sunday at 68 pcu/hour, the average traffic density is obtained in two days at 27.01 pcu/km, the average traffic flow speed is obtained in two days at 19.01 km/hour, the delay is obtained from the duration of the railroad crossing closing, the delay time is obtained from 2 minutes 96 seconds. The results of the relationship between speed and density on average for two days with the largest value using the greenshield method are 19.05 km/hour and the smallest is 12.84 km/hour, the relationship between volume and speed on average for two days with the largest value using the greenshield method is 210.211 pcu/hour and the smallest is 99.792 pcu/hour. After conducting shock wave analysis at the railroad level crossing, the results of the formed forward shock wave (wda) were 14.387 km/hour, the formed backward shock wave velocity (wab) was -1.118 km/hour, the recovery forward shock wave velocity (wdc) was 7.783 km/hour, the recovery backward shock wave velocity (wcb) was -7.763 km/hour, and the recovery shock wave velocity (wac) was 5.500 km/hour.